23 CALR Frameshift Mutation Detection in Myeloproliferative Neoplasms by Microfluidic Chip Analysis. (11th January 2018) - Greenwood, Michael; Newton, Keith; Pepper, Kristi; Hendrickson, Heather; Olsen, Randall J; Thomas, Jessica
Abstract: Calreticulin ( CALR ) mutation analysis is routinely used to diagnose BCR/ABL1-negative myeloproliferative neoplasms. The two most common CALR mutations are a 52-bp deletion (termed Type 1 mutation ) and a 5-bp insertion (termed Type 2 mutation ) in exon 9, which account for approximately 90% of cases. Detection of CALR mutations is most commonly performed using a cumbersome series of molecular techniques, including PCR amplification, capillary electrophoresis, and Sanger sequencing. The objective of this study was to develop, validate, and implement a novel assay to detect CALR mutations using microfluidic chip analysis. To evaluate our new microfluidic chip assay, we tested CALR mutant and wild-type specimens that were previously analyzed using conventional methods at a reference laboratory. Mutations included Type 1, Type 2, and two minor variant deletions. Samples included EDTA-anticoagulated peripheral blood and bone marrow specimens, air-dried bone marrow aspirate smears, and formalin-fixed paraffin-embedded bone marrow sections. CALR exon 9 was PCR amplified using two previously published primer pairs and a third unique primer pair that was custom designed for our new assay. Amplicons were sized using microfluidic chip analysis. Concordance with the reference method was 100% (42/42). Intrarun and interrun reproducibility was also 100% (3/3 and 3/3, respectively). The limit of detection was confirmed to be 6% mutant alleles. We determined that the microfluidic chip assay to detect CALR exon 9 mutations was acceptable for clinical use, and it has been implemented in our laboratory. Our assay generates rapid, accurate, and reproducible results. Compared to the conventional method, the microfluidic analysis assay benefits from a streamlined workflow, reduced turnaround time, and smaller instrument footprint.